2020
DOI: 10.1371/journal.pone.0241270
|View full text |Cite
|
Sign up to set email alerts
|

Household latrine utilization and associated factors in semi-urban areas of northeastern Ethiopia

Abstract: Background Latrine utilization is the actual behavior in a practice of regularly using existing latrines for safe disposal of excreta. Latrine utilization is a common problem in semi-urban areas of developing countries, including Ethiopia. Since the status of latrine utilization and associated factors among semi-urban areas of northeastern Ethiopia, including Alansha in South Wollo Zone is unknown, local data is needed in order to assess the need for planning of intervention programs for the improvement of lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 22 publications
6
39
4
Order By: Relevance
“…We confirmed that having more family members in the household was the risk factor for open defecation. Our finding agreed with earlier studies conducted in Ethiopia [ 25 ] and Ghana [ 26 ]. Households that have more members could be forced to go out for defecation due to overcrowding particularly during morning hours [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We confirmed that having more family members in the household was the risk factor for open defecation. Our finding agreed with earlier studies conducted in Ethiopia [ 25 ] and Ghana [ 26 ]. Households that have more members could be forced to go out for defecation due to overcrowding particularly during morning hours [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, household heads with unclean latrines were more likely to practice open defecation compared to those that had clean latrines or clean more frequently. Previous studies reported in Ethiopia [ 15 , 25 ] agreed with our finding. Latrines contaminated with excreta and other filthy matters discourage users to utilize the toilet [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, total latrine utilization was 56.1%. This study was consistent with a study conducted in North Ethiopia (54.9%), 3 but it was lower when compared to studies conducted in Kutaber District of the South Wollo Zone in northeastern Ethiopia (71.8%) 18 and Chencha District, GamoGofa, Ethiopia (67%). 19 This difference might be due to the difference in the implementation of the health extension package and the implementation time of CLTS approach in the study population.…”
Section: Discussionsupporting
confidence: 90%
“…It was not very different with the result from previous review study in Indonesia which revealed that the level of education, level of knowledge, and attitude are the variables that are most associated to ownership of latrine in Indonesia [49]. Then, another study in Ethiopia showed the demographic factors were significantly associated with availability of the toilet in the households [50]. Based on a study in Thailand, it shows that to overcome the latrine problem in the country it is necessary to make several important points such as a strong policy for latrine construction, integration of latrine development into health development, the right approach and strategy, adequate health facilities, and the will of the community [51].…”
Section: Resultscontrasting
confidence: 67%